AKT as a Therapeutic Target for Cancer - Song, Mengqiu; Bode, Ann M.; Dong, Zigang; Lee, Mee-Hyun (Cancer research (Chicago, Ill.), 2019)
Many cellular processes in cancer are attributed to kinase signaling networks. V-akt murine thymoma viral oncogene homolog (AKT) plays a major role in the PI3K/AKT signaling pathways. AKT is activated by PI3K or phosphoinositide-dependent kinases (PDK) as well as growth factors, inflammation, and DNA damage. Signal transduction occurs through downstream effectors such as mTOR, glycogen synthase kinase 3 beta (GSK3β), or forkhead box protein O1 (FOXO1). The abnormal overexpression or activation of AKT has been observed in many cancers, including ovarian, lung, and pancreatic cancers, and is associated with increased cancer cell proliferation and survival. Therefore, targeting AKT could provide an important approach for cancer prevention and therapy. In this review, we discuss the rationale for targeting AKT and also provide details regarding synthetic and natural AKT-targeting compounds and their associated studies.